Perancangan Komunikasi Visual Film Animasi Pendek “Sitiha dan Sisiti” - Wijaya, Fenny; Puspitasari, Dyah Gayatri (Bina Nusantara University, 2010)
The purpose of this research is to acquire, collect and analyze data needed to realize the design of short animated 3D films with a folklore theme which is presented with a visually appeal to interest spectators, especially children, so the moral message can be conveyed. The research method is to survey directly to the field, namely the cultural center of Indonesia TMII, playground and library. In addition to the literature media such as books, magazines and journals and supported with references from the internet media relating to the topic. Results to be achieved are for the moral message conveyed in this animated folklore film can be received and understood by the audience, especially children. Conclusion at the present time, visual communications media such as movies and television shows are very popular among children. So by using the medium of animated films, children will be more interested and may like local folklore again, since local productions are not of lesser quality than the outside impressions.